FACTORS AFFECTING ABNORMAL STOCK RETURNS ON LONG-TERM PERFORMANCE OF INITIAL PUBLIC OFFERING (IPO) (A Literature Review) - Kurniawan (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2021)
The average stocks return of the initial public offering (IPO) in the US stock market was - 29.13% at the end of the third year after the IPO (Ritter, 1991). The conclusion is that the Underperformed phenomenon is influenced by the volume of trade and only occurs in the non-financial sector (Ritter, 1991). Underperformed is a stock return of initial public offerings that have lower performance compared to the market return. Bessler and Thies (2007) stated that the year of going public is the time period of the initial public offering (IPO). There is a time variation in the pattern of benefits, it raises a question of whether companies can maximize the value and amount of funds acquired. In investing, investors consider the return and risk, the expected results of the investment will be realized after a certain period of time and during this period there is a risk of the investments made. The aim of this study is to analyze the factors that affect Abnormal Return on long-term stock performance after 36 months of the IPO. The independent variables in this study consist of Benchmark, Money Raised, Market Value, and Magnitude of Underpricing. The dependent variable is the abnormal return on long-term stock performance after 36 months of the IPO. The samples used in this study were the non-financial companies on 2010-2020 period as many as 54 non-financial companies using purposive sampling method. The analysis technique used was multiple linear regression analysis and performed classical assumption test which includes normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test.